Regulating Political Deepfakes in Indonesia: Democratic Governance and Electoral Integrity in Southeast Asia - Yasmin Aurelia Hapsari (Indonesian Political Transformation, 2025)
The rapid diffusion of generative artificial intelligence has introduced unprecedented challenges to democratic governance, particularly through the emergence of political deepfakes capable of manipulating public opinion and undermining electoral integrity. While scholarship on AI-generated disinformation has expanded rapidly in advanced democracies, limited attention has been devoted to emerging democracies where digital literacy, regulatory capacity, and electoral institutions remain uneven. This study examines Indonesia’s regulatory response to political deepfakes within the broader context of democratic governance in Southeast Asia. Employing a qualitative case study approach, the research analyzes Indonesia’s legal framework governing digital information, electoral regulations, AI-related policies, and institutional responses during the 2024 general election. Documentary analysis is complemented by interviews with policymakers, election officials, civil society organizations, and digital platform experts to identify governance gaps and regulatory challenges. The findings are expected to demonstrate that existing legal instruments addressing misinformation are insufficient to cope with AI-generated synthetic media because they were designed for conventional forms of digital manipulation. Furthermore, fragmented institutional coordination and limited technological capacity constrain effective enforcement. The article argues that regulating political deepfakes requires an integrated governance model combining adaptive legislation, platform accountability, AI detection mechanisms, public digital literacy, and regional cooperation among Southeast Asian democracies. By positioning Indonesia as an important case within the Global South, this study contributes to emerging debates on AI governance, electoral integrity, and democratic resilience. The findings offer policy recommendations for balancing freedom of expression with the protection of democratic processes in increasingly AI-mediated political environments.